Relationship between family connectedness and nutritional status among under-five children in Jember Regency of Indonesia - Rofiatul Nur Jannah; Tantut Susanto; Latifa Aini Susumaningrum; Mokhlas Kholidi (Journal of Community Empowerment for Health, 2022)
The family has an important role to fulfill the nutritional requirements for their children. As changes in the family life cycle develop, every step involved in the tasks of family development is influenced by family interconnectedness. The objective of this study was to identify the correlation between family connectedness and nutritional status among under-five children in Public Health Center of Panti, Jember Regency of Indonesia. A cross-sectional sectional study was conducted among 307 families who have children aged 2-5 years using consecutive sampling. A self-administered questionnaire was used to measure sociodemographics of the parents and their under-five children, while the Parent-Child Relationship Questionnaire was use to assess the quality of family connectedness. Standing scales were used to measure the body weight of the under-five children. A chi-square test was used to analyze the data. The results showed that among 307 parents, the family connectedness of parents and nutritional status of under five children were in the moderate (63.8%) category and good nutrition (58.6%) status, respectively. There was a significant relationship between family connectedness and nutritional status among <five aged children (X2=8,679;  p-value = 0.013). These results demonstrate there is a relationship between family connectedness with the nutritional status of children 2-5 years old. Further research is recommended to analyze other variables that can affect the nutritional status of under–five children.